Predicting the acceptance of cloud computing in higher education institutions by extending the technology readiness theory / Mohd Talmizie Amron, Nur Hidayah Md Noh and Mohamad Amiruddin Mohamad - Amron, Mohd Talmizie; Md Noh, Nur Hidayah; Mohamad, Mohamad Amiruddin (Universiti Teknologi MARA, 2022)
The COVID-19 outbreak has impacted almost every facet of life, including education. Technology has almost entirely replaced conventional face-to-face teaching and learning environment. This public health calamity has hastened the digitisation of education, which was previously only provided without a repellent component. Cloud computing is widely used in education, notably higher education, to provide online access and share teaching resources, educational information, notes, lectures, and academic assessments. But, while observing technology's grandeur, are people prepared to accept an avalanche of information resources and open online access via cloud-based services? Thus, this study investigated users' readiness and acceptability of cloud computing in Higher Education Institutions (HEIs). Using the Structural Equation Modelling analysis, this study surveyed 470 individuals from Malaysian HEIs using the Technology Acceptance Model and Technology Readiness Index models. Perceived Ease of Use and Perceived Usefulness is positively relevant in understanding why a user chooses cloud computing. The environment of the learning process and the security factors are positive predictors of cloud computing use intention. Optimism and Innovativeness have been demonstrated to impact technology acceptance factors substantially. On the other hand, Discomfort and Insecurity do not affect technology acceptance, except for Insecurity, which negatively affects Perceived Usefulness. This research adds to the growing knowledge about technology readiness and acceptance, especially after a pandemic hits the world.